Soft corruption : how unethical conduct undermines good government and what to do about it - Schluter, William E., 1927- (Rivergate regionals., 2017)
New Jersey has long been a breeding ground for political corruption, much of it perfectly legal. In Soft Corruption, a former state senator recounts his fifty-year fight to expose such misconduct. William E. Schluter doesn't simply wade through New Jersey's muck, but provides concrete suggestions for how our political system might be reformed and how citizens can effect that change.